The Estimation and Relationship of Domestic Electricity Consumption and Appliances Ownership in Malaysia Intermediate City - Sharif Ali, Sharif Shofirun; Razman, Muhammad Rizal; Awang, Azahan (International Journal of Energy Economics and Policy, 2020)
The growing trend of energy consumption in urban area has created negative impacts to the urban environment because the issues related to energy use and urban developments are largely dependent on human aspects and mobilized by the inhabitants of the city itself. This study aims to estimating the electricity consumption with regards to electrical appliances usage and carbon emissions in domestic sector of urban area. The study revealed that average electricity power consumption was 648.31 kWh. Meanwhile, refrigerator and air conditioning recorded as the highest electricity consumption appliances compared to other appliances. In terms of type of house, household from bungalow house consumed more electricity power and resulted to high carbon emissions compared to other households. The study suggested that the level of knowledge, awareness, commitment, attitude and behavior of electricity consumption among household should be intensified. Besides, the number of energy saving appliances also needs to be improved and encourage smart energy consumption that led to the sustainable urban development. Keywords: Electricity Consumption; Appliances; Carbon Emissions JEL Classifications: Q40; R20 DOI: https://doi.org/10.32479/ijeep.8358